Life behind the 'Pink' Bars : an exploratory study on the lived experiences of female inmates in Changi Women's Prison - Boh, Xuan Qi (2018)
This paper focuses on the interaction between the carceral system and its occupants, to explore the lived experiences of female inmates during their incarceration in Changi Women’s Prison. Drawing information from 10 female ex-inmates in Singapore through semi-structured interviews, this paper discusses about the prison settings through an insider’s perspective. An analysis of the interviews revealed three major themes: challenges faced by the inmates during their incarceration, how these problems were negotiated and mitigated, and the impact of the prison sentence on the inmates. The findings also uncovered how the Foucauldian concept on “docile bodies” is contested, and how the General Strain Theory by Agnew plays out in the carceral scene. This paper aims to serve as an addition to the limited research that has been done on female inmates in Singapore, and hopefully be able to provide guidance on the areas that can be modified in the penal space.